Insect pests incidence and variations due to forest landscape degradation in the humid forest zone of southern Cameroon: farmers perception and need for adopting an Integrated Pest Management strategy - Kekeunou, S.; Messi, J.; Weise, Stephan F.; Tindo, M. (2006)
Group surveys were conducted in five villages in each of the three resource-use zones of the humid forest zone of Southern Cameroon, to assess insect pests’ incidence and the variation due to forest landscape degradation in the agricultural production systems. 389 farmers were interviewed. The results show that: (1) In annual crop systems, insect pests in general rank together with vertebrate pests and diseases amongst the most important agronomic constraints. No differences were found between the intensification zones, except for weeds, which appeared to be a greater constraint in the slightly degraded area. Within the insect pest, the greatest damage to crops according to farmers originated from borers and scales, followed by variegated grasshopper. Only the termites showed a difference between zones - the problem being greatest in the high-degraded areas. (2) In the young perennial crop systems, all the categories of agronomic constraints were equally important. Within the insect pest, mirids were identified as the greatest constraint, followed by borers and caterpillars. There were more variations in the responses according to zones compared to annual crops. Termites and scales were relatively more important in the high-degraded area. In term of control strategy, we recommended an integrated pest management.